2023
DOI: 10.1161/hypertensionaha.123.21408
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma IgG N -Glycome Profiles Reveal a Proinflammatory Phenotype in Chronic Thromboembolic Pulmonary Hypertension

Abstract: BACKGROUND: The pathological mechanism of chronic thromboembolic pulmonary hypertension (CTEPH) is not fully understood, and inflammation has been reported to be one of its etiological factors. IgG regulates systemic inflammatory homeostasis, primarily through its N -glycans. Little is known about IgG N -glycosylation in CTEPH. We aimed to map the IgG N -glycome of chronic thromboembolic pulmonary hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…36 Moreover, our preliminary research found that the IgG N-glycome in CTEPH presented a proinflammatory phenotype (upregulated IgG-Gal ratio representing decreased IgG galactosylation) compared with healthy controls, and the IgG-Gal ratio is positively correlated with the level of NT-proBNP. 35 In the current study, we found that patients in the CHIP group showed a severe inflammatory state, reflected by the upregulated IgG-Gal ratio, compared with that in the non-CHIP group, suggesting a probable relationship between CHIP and the secreted IgG antibody phenotype. However, the causality and directionality of the link between the proinflammatory functions of IgG and CHIP require further investigation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…36 Moreover, our preliminary research found that the IgG N-glycome in CTEPH presented a proinflammatory phenotype (upregulated IgG-Gal ratio representing decreased IgG galactosylation) compared with healthy controls, and the IgG-Gal ratio is positively correlated with the level of NT-proBNP. 35 In the current study, we found that patients in the CHIP group showed a severe inflammatory state, reflected by the upregulated IgG-Gal ratio, compared with that in the non-CHIP group, suggesting a probable relationship between CHIP and the secreted IgG antibody phenotype. However, the causality and directionality of the link between the proinflammatory functions of IgG and CHIP require further investigation.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, our previous study suggested that the IgG N-glycan characteristics of patients with CTEPH presented an obvious proinflammatory phenotype (decreased proportion of IgG-Gal leading to a higher IgG-Gal ratio). 35 Decreased IgG galactosylation has been reported to be a hallmark of inflammation. 36 In the present study, baseline IgG glycan characteristics were analyzed in patients with and without CHIP mutations.…”
Section: Association Of Chip With Inflammatory Biomarkersmentioning
confidence: 99%
“…Especially, clinical IgG N-glycosylation analysis does not rely as heavily on mild serum/plasma storage conditions and timely analysis (glycans are even stable at 50 °C for two weeks) as many other omics analyses. 54 It is worth mentioning that the high-throughput workflow for IgG N-glycome profiling applied in the present study has been widely used in various studies, [24][25][26][27]55 enabling the candidate glycan biomarker to be more convenient for further clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The formulas used for the calculation: Galactosylation = H3N4F1/(H4N4F1 + 2*H5N4F1); Bisecting N- acetylglucosamine = H3N5F1 + H4N5F1 + H5N5F1; Fucosylation = H3N4F1 + H4N4F1 + H3N5F1 + H5N4F1 + H4N5F1 + H5N5F1 (H = hexose; N = N-acetylhexosamine; F = deoxyhexose [fucose]). 24,27 GlycoWorkbench software (version 1.1.3480) was used to annotate the N-glycan structures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation